Perspectives of the services provided by the human resource function - Jay Owens; Joan Van Der Merwe (South African Journal of Business Management, 1993)
The aim of the research was to study organizational perceptions of the quality of service rendered by human resource directors. In this article we focus on the service of equipping first-line managers for their human resource function. Key abilities and skills required by first-line managers were identified in the literature and verified in eight interviews. These were included in the questionnaire to focus the thinking of respondents. Forty questionnaires were received from a stratified sample of directors and managers of ten organizations. Respondents were requested to rate the service quality attributes as defined by Parasuraman, Zeithaml Berry in terms of the service provided by the human resource function. Rated service quality determinants were modelled on Thurstone's Case V Scale Model, yielding a unidimensional interval scale from comparative judgements. Measurement of the perceived service quality was a starting point in defining deficiencies in the service orientation of the human resource function.
Keywords: 650